Phytotoxic Impact of Mesquite (Prosopis juliflora) Pericarps on Seed Germination and Seedling Growth of Lettuce (Lactuca sativa) (University of Khartoum Journal of Agricultural Sciences, 2023)
Phytotoxic effects of mesquite (Prosopis juliflora) pericarps onseed germination and seedling growth of lettuce (Lactuca sativa) wereinvestigated. Aqueous extracts of 10, 20, 30, 40, 50 and 60 g of drymesquite pericarps in a litre of distilled water were used. Final seedgermination percentage and germination rate, evaluated with correctedgermination rate index, and days to 50% of the final seed germination,were significantly reduced. Likewise were the radicle and the hypocotyllengths, five days after germination. The magnitude of the reductionincreased with the increase of extract concentration. Mannitol solutionswith the same osmotic potential and pH as the aqueous extracts resulted insignificantly higher values of these traits than their correspondingextracts. This indicates that mesquite pericarp contains allelochemicalswhich could detrimentally affect seed germination and seedling growth oflettuce.
Keywords: Mesquite; lettuce; allelopathy; pericarp